Fault-tolerant backup storage system for confidential data in distributed servers - Olzhas Tasmagambetov; Yerzhan Seitkulov; Ruslan Ospanov; Banu Yergaliyeva (Universitas Ahmad Dahlan, 2023)
This article addresses the critical issue of securing backup storage for confidential data, a key concern in safeguarding the operations of critical information systems dealing with extensive amounts of sensitive information. The study proposes a novel cryptographic fault-tolerant backup storage system for confidential data, leveraging cryptographic algorithms and protocols. These protocols enable message encryption, ensuring decryption is only possible after a specified time period. The proposed system combines various distributed key generation protocols, proactive secret sharing protocols, asymmetric encryption algorithms, and digital signature algorithms. By employing such cryptographic protocols, it becomes feasible to develop and implement a robust, fault-tolerant service for backing up confidential data.